2022
DOI: 10.1371/journal.ppat.1010605
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and dissemination of avian-origin influenza A virus within the northern Atlantic Flyway of North America

Abstract: Wild waterbirds, the natural reservoirs for avian influenza viruses, undergo migratory movements each year, connecting breeding and wintering grounds within broad corridors known as flyways. In a continental or global view, the study of virus movements within and across flyways is important to understanding virus diversity, evolution, and movement. From 2015 to 2017, we sampled waterfowl from breeding (Maine) and wintering (Maryland) areas within the Atlantic Flyway (AF) along the east coast of North America t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…The re-introduction of new viruses and recurring local expansions of divergent or reassortant HPAI viruses within the East Coast of Canada and the USA could impact the genetic landscape within the North American flyways. Moreover, the continued movements of birds through the North American flyways that consist of three hotspots for avian influenza virus, the Delaware Bay for shorebirds and gulls, Alberta for ducks, and Chesapeake Bay, wherein millions of birds congregate, may have long-term consequences for virus diversity and new variant generation [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The re-introduction of new viruses and recurring local expansions of divergent or reassortant HPAI viruses within the East Coast of Canada and the USA could impact the genetic landscape within the North American flyways. Moreover, the continued movements of birds through the North American flyways that consist of three hotspots for avian influenza virus, the Delaware Bay for shorebirds and gulls, Alberta for ducks, and Chesapeake Bay, wherein millions of birds congregate, may have long-term consequences for virus diversity and new variant generation [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dissemination of AIVs within and across regions is largely influenced by the migratory movements of wild birds, which can carry and exchange different virus strains along their flyways [ 27 ]. Flyways are large corridors that connect migratory birds’ breeding and wintering grounds across continents [ 27 ].…”
Section: Virus Disseminationmentioning
confidence: 99%
“…The dissemination of AIVs within and across regions is largely influenced by the migratory movements of wild birds, which can carry and exchange different virus strains along their flyways [ 27 ]. Flyways are large corridors that connect migratory birds’ breeding and wintering grounds across continents [ 27 ]. Studies have shown, for example, that the Pacific Flyway, a migratory path connecting western North America to eastern Asia via breeding grounds in Beringia, has the potential to introduce or exchange avian influenza viruses between North America and Asia [ 27 ].…”
Section: Virus Disseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly pathogenic avian influenza (HPAI) subtype H5NX, clade 2.3.4.4b has been responsible for several outbreaks worldwide causing multiple mass mortality events among avian wildlife and marine mammal populations (Charostad et al, 2023). The wide and fast dispersion of this virus is attributed to the contamination of migratory species (Caliendo et al, 2022a; Prosser et al, 2022; Gass Jr et al, 2023) and those with long-range dispersing capabilities (Boulinier, 2023; Lane et al, n.d.). On the other hand, the H5 highly pathogenic strains have undergone extensive evolution.…”
Section: Introductionmentioning
confidence: 99%